Body Image Overview of Emerging Adult K-Pop Leaders: Gambaran Citra Tubuh pada Emerging Adult Penggemar K-Pop - Pratiwi, Mega Yuniar; Iriani, Ririn Dewanti Dian Samudra (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the body image of K-Pop fans on Twitter, with descriptive quantitative type of research being used. The research population is K-Pop fans who are in the developmental range of Emerging Adulthood (18 – 25 years), and the samples obtained are used as research subjects (186 individuals), with incidental sampling technique used. The data collection technique uses a Likert-type psychological scale which was compiled by the author herself based on the body image theory proposed by Brown, Cash, & Mikulka, and the reliability of each dimension are: 1) appearance evaluation: 0.872, 2) appearance orientation: 0.802, 3) body area satisfaction: 0.959, 4) overweight preoccupation: 0.573, and 5) self-classified weight: 0.883. The results of data analysis showed that the body image of 29 (15.6%) research subjects was in the low category, 135 (72.6%) were in the medium category, and 22 (11.8%) were in the high category.